Development of the design of mobile solar power plant - P. I. Savelov; Yu. E. Livshic (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The purpose of the work is to develop the design of a mobile solar power plant with automatic biaxial positioning of solar cells. The authors have developed the algorithm for the operation of a mobile solar power plant and the design of the control unit for the solar cell positioning system. Research and development of a solid-state model of the mobile solar power plant were done using the SolidWorks computer-aided design system. The design optimization for the solar power plant was carried out using computer engineering research. The design optimization of the parts was carried out by the method of generative design. Optimization of the control unit layout was carried out according to the results of studying the thermal processes that occur during steady-state operation using the Flow Simulation SolidWorks research module. It is established that the natural air cooling of the electronic control unit of the mobile solar power plant with this arrangement of elements is optimal and sufficient to ensure its operation in climatic zone B1. The design of the control unit housing ensures IP66 protection. The effect of wind load on the strength characteristics of load-bearing structures has been investigated. The research has established pressurized and turbulence zones, the value of equivalent stresses and deformations in load-bearing structures when exposed to wind speeds of up to 8 points (15 m/s) on the Beaufort scale. The design and materials of the supporting structures of the mobile solar power plant are determined taking into account minimum weight and dimensions, strength characteristics and ease of transportation. Using generative design, a topological analysis of the load-bearing elements of the mobile solar power plant was carried out, which allowed the reduction of their mass by 30 % while maintaining the required design strength.